Role of complementary and alternative medicine in geriatric care: A mini review - Siddiqui, Mohammad Jamshed; Min, Chan Sze; Verma, Rohit Kumar; Jamshed, Shazia Qasim (Pharmacognosy Reviews)
Since time immemorial homo sapiens are subjected to both health and diseases states and seek treatment for succor and assuagement in compromised health states. Since last two decades the progressive rise in the alternative form of treatment cannot be ignored and population seems to be dissatisfied with the conventional treatment modalities and therefore, resort to other forms of treatment, mainly complementary and alternative medicine (CAM). The use of CAM is predominantly more popular in older adults and therefore, numerous research studies and clinical trials have been carried out to investigate the effectiveness of CAM in the management of both communicable and non‑communicable disease. In this current mini review, we attempt to encompass the use of CAM in chronic non‑communicable diseases that are most likely seen in geriatrics. The current review focuses not only on the reassurance of good health practices, emphasizing on the holistic development and strengthening the body’s defense mechanisms, but also attempts to construct a pattern of self‑care and patient empowerment in geriatrics. The issues of safety with CAM use cannot be sidelined and consultation with a health care professional is always advocated to the patient. Likewise, responsibility of the health care professional is to inform the patient about the safety and efficacy issues. In order to substantiate the efficacy and safety of CAMs, evidence‑based studies and practices with consolidated standards should be planned and executed.
Keywords: Complementary and alternative medicine; geriatric; non‑communicable diseases